Mimicking nature: Self-strengthening properties in a dental adhesive. (15th April 2016) - Song, Linyong; Ye, Qiang; Ge, Xueping; Misra, Anil; Spencer, Paulette
Graphical abstract: Abstract: Chemical and enzymatic hydrolysis provoke a cascade of events that undermine methacrylate-based adhesives and the bond formed at the tooth/composite interface. Infiltration of noxious agents, e.g. enzymes, bacteria, and so forth, into the spaces created by the defective bond will ultimately lead to failure of the composite restoration. This paper reports a novel, synthetic resin that provides enhanced hydrolytic stability as a result of intrinsic reinforcement of the polymer network. The behavior of this novel resin, which contains γ-methacryloxyproyl trimethoxysilane (MPS) as its Si-based compound, is reminiscent of self-strengthening properties found in nature. The efforts in this paper are focused on two essential aspects: the visible-light irradiation induced (photoacid-induced) sol–gel reaction and the mechanism leading to intrinsic self-strengthening. The FTIR band at 2840 cm −1 corresponding to CH3 symmetric stretch in –Si–O–CH3 was used to evaluate the sol–gel reaction. Results from the real-time FTIR indicated that the newly developed resin showed a limited sol–gel reaction (<5%) during visible-light irradiation, but after 48 h dark storage, the reaction was over 65%. The condensation of methoxysilane mainly occurred under wet conditions. The storage moduli and glass transition temperature of the copolymers increased in wet conditions with the increasing MPS content. The cumulative amounts of leached species decreased significantly when the MPS-containing adhesive was used. The results suggest that the polymethacrylate-based network, which formed first as a result of free radical initiated polymerization, retarded the photoacid-induced sol–gel reaction. The sol–gel reaction provided a persistent, intrinsic reinforcement of the polymer network in both neutral and acidic conditions. This behavior led to enhanced mechanical properties of the dental adhesives under conditions that simulate the wet, oral environment. Statement of Significance: A self-strengthening dental adhesive system was developed through a dual curing process, which involves the free radical photopolymerization followed by slow hydrolysis and condensation (photoacid-induced sol–gel reaction) of alkoxylsilane groups. The concept of "living" photoacid-induced sol–gel reaction with visible-light irradiation was confirmed in the polymer. The sol–gel reaction was retarded by the polymethacrylate network, which was generated first; the network extended the life and retained the activity of silanol groups. The self-strengthening behavior was evaluated by monitoring the mechanical properties of the hybrid copolymers under wet conditions. The present research demonstrates the sol–gel reaction in highly crosslinked network as a potentially powerful strategy to prolong the functional lifetime of engineered biomaterials in wet environments.